Do Large Estates Benefit Smallholder Neighbours? Evidence from Malawi. Issue 4 (3rd April 2023) - Joseph, Julian; van Dijk, Michiel; Krisztin, Tamás
Abstract: We examine spillovers from agricultural estates to Malawian smallholders within an econometric counterfactual framework. We consider economic spillovers such as income, as well as agrarian spillovers such as yields, harvests, and crop diversity. We identify long-run effects of large agricultural investments on small-scale farmers. For the location of large estates, we use a novel OpenStreetMap dataset, while data on smallholder's stems from a household survey. We provide evidence for the importance of the distance threshold for spillovers, and explore multiple thresholds. In proximity to estates we find higher groundnut and pigeon pea yields and increased crop diversity. In very close proximity, incomes are also higher. Area under cultivation in total and for maize are smaller for nearby households, while maize yields are not significantly different. Overall, our results suggest that policies should aim to leverage the increased crop diversity and groundnut yields while mitigating potential detrimental effects arising from reduced cultivated land.